How people living with motor neurone disease and their carers experience healthcare decision making: a qualitative exploration. Issue 13 (19th June 2022) - Paynter, C.; Mathers, S.; Gregory, H.; Vogel, A. P.; Cruice, M.
Abstract: Purpose: Healthcare decision making in motor neurone disease (MND) focuses on symptom management and quality of life. Decision making may be affected by personal approach to receiving information, decision making style, and disease symptoms. This study explored decision making from the perspectives of people living with motor neurone disease (plwMND). The issues impacting engagement and involvement in healthcare decisions were investigated. Methods: Semi-structured interviews were conducted with 19 plwMND and 15 carers. Interview data was inductively analysed to identify and describe patterns and themes. Results: Data analysis identified six overarching themes: Dimensions of decision making; Window of opportunity for choice; Intrinsic influences on decision making; Extrinsic influences impacting decision making; Planning in uncertainty; and, Communication is core. Many participants did not identify a process of "decision-making" except if considering early gastrostomy placement. Information provision requires a balance between ensuring patients are informed but not overwhelmed. Communication impairment impacts involvement. Healthcare professionals' communication style influences engagement in decision making. Conclusion: PlwMND perceive a lack of clinical decisions to make because disease symptoms and clinical phenotypes dictate necessary interventions. PlwMND describe communication impairment as a barrier to involvement in decision making and extra support is required to ensure they maintain engagement. IMPLICATIONS FOR REHABILITATION: People living with MND (plwMND) perceive they have few clinical decisions to make and viewed this process as "accepting a recommendation", rather than "making a decision" although early gastrostomy placement is the exception with considerable deliberation evident. Specialist multidisciplinary clinic advice is especially helpful for plwMND without dysphagia (swallowing problems) when considering early gastrostomy placement. Communication impairment may be a barrier to involvement in healthcare decisions and extra support to remain engaged is required. Some plwMND choose not to involve others in their decisions, and patients/families with medical or scientific backgrounds are more likely to collaborate with each other outside the context of clinic appointments.